Natural Language Processing Dalam Memperoleh Informasi Akademik Mahasiswa Universitas Atma Jaya Makassar - Lisangan, Erick Alfons (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
The information has become one of the most important parts for an institution today, including Universitas Atma Jaya Makassar. One of the information is academic, so it needs fast processing to get that information. The problems that arise are difference of language between the user who need information and database language which storage data of academic. So we need an interpreter to bridge the difference of language. In this research, the writer uses Natural Language Processing as the solution from that problem and use Parser Noise-Disposal. The application is designed by PHP as programming language and MySQL as database.